Analisis Penanganan Kerusakan Jalan Menggunakan Metode Pavement Condition Index di Jalan Jepang Kabupaten Kapuas - Dendy Giovany Zevanya; Murniati; Devia (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Roads are an important factor in economic growth and regional development. However, high traffic volumes can lead to deterioration in road quality, such as damage to the surface. In Kapuas Regency, particularly on the Jepang roads, damage is often caused by vehicles, especially trucks, which exceed the load limits. Proper road maintenance is needed to repair and prevent further damage, with a focus on assessing the nature of the damage. A planned maintenance programme will support smooth transport and the regional economy. The research was carried out in Kapuas Regency, specifically on Jepang roads, using the Pavement Condition Index (PCI) method, which is used to determine the pavement condition index on a scale of 0 to 100, which is used to assess road conditions based on the level of damage. The research results show that Jepang roads have an average PCI of 79.2, which is in the very good category. Based on the PCI method, this road requires routine maintenance to prevent more serious damage in the future.